Piezoelectric tube as resonant transducer for gas-phase photoacoustics - Kanchalar Keeratirawee; Peter C. Hauser (My University, 2020)
The use of a piezoelectric tube for the photoacoustic gas-phase determination of NO2 as a model analyte is demonstrated. The tube is made from lead zirconate titanate with 30 mm length and 5.35 mm internal diameter. Its inner and outer surfaces are coated with electrodes. The tube serves as both, resonance body and transducer. The design is thus simpler than the usual combination of resonance tube and microphone as the two functions are embodied in the same component. The main resonance frequency of the tube was found to be 5341 Hz. A blue laser diode emitting at 450 nm was employed as light source for the determination of NO2. The limit of detection was determined as 83 ppbV and the calibration curve was linear with a coefficient of determination (r2) of 0.9998 up to the highest concentration of 15 ppmV tested.
Keywords: Lead zirconate titanate; Spectroscopy and Laser Applications